Seasonal variation of flavonoids in Teucrium polium L. (Lamiaceae) - Gjoshe Stefkov; Marija Karapandzova; Marina Stefova; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2009)
Тhe aim of the present study was identification of flavone aglycones and determination of the content of each and the content of total flavonoids as well as investigation of the eventual seasonal variations of flavonoids in Teucrium polium L. (Lamiaceae). The plant samples were collected at six different locations in Republic of Macedonia, during summer in 1999, 2000 and 2003. For determination of seasonal variations, the samples were collected in v. Koleshino, in 2004, each month during the whole season. Six flavone aglycones (luteolin, apigenin, diosmetin, cirsiliol, cirsimaritin and cirsilineol) were identified in the hydrolyzed extracts of the over ground part of Teucrium polium by HPLC method. The most abundant flavone was luteolin, followed by apigenin and cirsimaritin. Great seasonal variations were found in the content of each and in the content of total amount of flavonoids. The most abundant flavone during the whole season was luteolin with the highest content in May. The content of total flavonids was the highest in the period from May to July, which could be recommended as the most convenience period in the season for collecting of the plant material from Teucrium polium.